Survey-Based Research of Knowledge and Perception of Endodontic Treatment on an Indian Subpopulation - Saji, Shalin Ann; Shetty, Chitharanjan; Shetty, Aditya; Hegde, Mithra N. (Journal of Health and Allied Sciences NU, 2021)
Objective To assess the patients' knowledge and perceptions regarding endodontic treatment.Materials and Methods A questionnaire-based survey was conducted in a group of 400 patients, consisting of questions based on sociodemographic details as well as their knowledge about endodontic treatment. The collected data was tabulated and analyzed using methods of descriptive analysis.Results The majority of the respondents stated their level of knowledge regarding endodontic treatment as average.Conclusion Within the limitations of the study, an improvement in the knowledge regarding endodontic treatment among patients was observed.Clinical Significance Population-based surveys are useful for evaluating the community and patients' mentality toward endodontic treatment. Proper information regarding the treatment modalities can be explained to the patient based on their lack of information, which is of utmost importance to develop a positive approach to root canal treatment.
Keywords: Fear; Pain; Questionnaire; Root canal treatment